2012
DOI: 10.1007/s10815-012-9868-x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of high-magnification sperm morphology examination on ICSI outcomes in the presence of oocyte dysmorphisms

Abstract: Purpose To evaluate the relationship between oocyte dysmorphisms and IMSI outcomes Methods Data of IMSI cycles performed in 332 patients were included in this study. Patients were included only if presented more than four and less than 30 oocytes upon oocyte retrieval. Patients who underwent IMSI were matched, concerning female age and sperm parameters, with patients who underwent ICSI in the same period (n0332). The two groups (ICSI and IMSI) were compared with regard to treatment outcomes. The influence of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In this study, fertilization rates, D3 and D5 embryo quality was found to be much better in Intracytoplasmic morphologically selected sperm injection (IMSI) than Intracytoplasmic sperm injection (ICSI). In this study, it is also said that good results were achieved when oocyte morphology was also included in evaluation [17,18]. There are similar studies as our's and also at the present time sperm DNA fragmentation is performed in many centers but still the choice for treatment is determined by a simple sperm parameters analysis in many technologically insufficient centers.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, fertilization rates, D3 and D5 embryo quality was found to be much better in Intracytoplasmic morphologically selected sperm injection (IMSI) than Intracytoplasmic sperm injection (ICSI). In this study, it is also said that good results were achieved when oocyte morphology was also included in evaluation [17,18]. There are similar studies as our's and also at the present time sperm DNA fragmentation is performed in many centers but still the choice for treatment is determined by a simple sperm parameters analysis in many technologically insufficient centers.…”
Section: Discussionsupporting
confidence: 64%
“…We found no difference in embryo morphology. Except for two studies [23,28], IMSI does not improve the morphology of early embryos [14,19,21,22,29]. However, an increase of development at the blastocyst stage using IMSI has been demonstrated by some authors [28,30,31], although randomization at the oocyte level did not confirm this finding [22].…”
Section: Nsmentioning
confidence: 94%